Quantifying presence using calling patterns - Husna, Husain; Phithakkitnukoon, Santi; Baatarjav, Enkh-Amgalan; Ram Dantu (Communication Systems Software and Middleware and Workshops, 2008. COMSWARE 2008. 3rd International Conference on, 2008)
Presence technology is going to be an integral part of the next generation of communication technology. It can eliminate telephone tag between two parties (caller and callee), which will increase productivity of the parties and reduce unnecessary bandwidth usage of unwanted calls. In this paper, we propose a Willingness Estimator that computes willingness level of a callee for receiving calls from a specified caller. By knowing the willingness value of the callee the caller can decide on proceeding with the call or not. The proposed Willingness Estimator is tested with real mobile user data, and these results are highly accurate. We measure willingness based on calling patterns (arrival time, location, day) of a caller to a callee and this could serve as one of the future presence based services. The results can be used in telecommunication networks such as PSTN, Cellular networks, and Voice over IP networks.
Keywords: cellular networks; Communications technology; Computer science; Computer security; Intrusion detection; Laboratories; Mobile handsets; mobile user data; Network servers; next generation communication; Next generation networking; presence technology; Productivity; PSTN; telecommunication networks; telephony; user calling pattern; voice over IP networks; willingness estimator

Goliath: A Configurable Approach for Network Testing - Fagen, Wade; Cangussu, João; Ram Dantu (Testbeds and Research Infrastructure for the Development of Networks and Communities, 2007. TridentCom 2007. 3rd International Conference on, 2007)
When testing a network environment and/or application many aspects need to be taken into consideration. For example, different software needs to be deployed at different nodes and different topologies may also need to be tested. The manual execution of these tasks are very time consuming and a configurable environment to facilitate these tasks and consequently improve testing performance is desired. In this paper a virtual network environment that can be easily reconfigured is presented to address this problem. Also presented is a case study with the results of deployment and containing a worm propagation attack.
Keywords: automated network testing; Computational modeling; computer networks; Computer science; Computer worms; Distributed computing; Goliath; Intrusion detection; network topologies; Network topology; Protocols; security of data; Software testing; System testing; telecommunication computing; telecommunication network topology; telecommunication security; virtual network environment; virtual private networks; worm propagation attack